Optimizing Oversight: Developing an Ideal Framework for Supervision Prisoners’ Rights Allocation - Anis Widyawati; Dian Latifiani; Helda Rahmasari; Ade Adhari (IJCLS (Indonesian Journal of Criminal Law Studies), 2024)
This study analyzes the problem of a prosecutor’s procrastination in executing a court judgment that delays the prisoners’ serving their sentences and causes some irregularities in the correctional facilities regarding the prisoners’ rights trade. The introduction of many prisons without a specific body to supervise the execution of the sentence, particularly the warded people’s freedom in Indonesia, appeared to have unfulfilled justice in the society. In this regard, this research aims to define the validity of the need to enhance the Supervision of prisoners’ rights protection in Central Java. It describes an optimal system relevant to such Supervision. The type of research that was utilized in this study is sociological juridical. Sociological juridical research serves to be the opposite of normative legal research. It is revealed that there have been ongoing infringements of prisoners’ rights, highlighting the further need to set a more comprehensive mechanism that would include the Police, the Prosecutors, the Courts, and the Correctional Institutions in the system of oversight and other management functions. Every level in the hierarchy system of the Criminal Justice System has its limit on including the human rights of prisoners containing adequate risks of intrusion, where checks and balances must be exercised. Formally and horizontally, these rights must be assured and upheld both legally and in their spirit by Justice and the Law. This study’s findings are that appropriate measures need to be applied to implement better Supervision policies aimed at safeguarding the human rights of prisoners and ensuring the justice system in Indonesia is not compromised.